Effect of solvent quality on Poiseuille flow of polymer solutions in microchannels: A dissipative particle dynamics study. Issue 15 (17th December 2018) - Xu, Shaofeng; Lou, Yinghou; He, Ping; Wang, Xiangyang; Wang, Jiugen
ABSTRACT: The Poiseuille flows of polymer solutions for varying quality solvents in microchannels have been simulated using dissipative particle dynamics. In particular, the velocity distributions and the polymer migration across the channel have been investigated for good, athermal, and poor solvents. The velocity profiles for all three kinds of solvent deviate from the parabolic profile, and the velocity profile of the athermal solvent falls in between the good solvent and the poor solvent. For the athermal solvent, a migration away from the wall due to the hydrodynamic interactions between the chains and the wall is observed, and a migration away from the channel center due to the different chain Brownian diffusivities is also observed. For the good solvent, because of the more stretched polymer chains, the migration away from the wall is stronger than that for the athermal solvent. However, the migration away from the channel center is not observed for good solvents. For the poor solvent, the hydrodynamic interaction within the chains is screened, and the polymer chains migrate toward the wall and appear to be absorbed by the wall. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47345. Abstract :